Answer:
2CH3SH(l) + CO (g) → CH3CO(SCH3)(l) +H2S (g)
8H2S(g) + 8CO(g) → 4CH3CO2H(g)+ S8(s)
Explanation:
Step 1: The unbalanced equation
CH3SH(l) + CO (g) → CH3CO(SCH3)(l) +H2S (g)
Step 2: Balancing the equation
CH3SH(l) + CO (g) → CH3CO(SCH3)(l) +H2S (g)
On the left side we have 1x S, on the right side we have 2x S (1x in CH3CO(SCH3) and 1x in H2S). To balance the amount of S, we have to multiply CH3SH on the left side by 2. Now the equation is balanced.
2CH3SH(l) + CO (g) → CH3CO(SCH3)(l) +H2S (g)
Step 1: The unbalanced equation
H2S(g) +CO(g) → CH3CO2H(g)+ S8(s)
Step 2: Balancing the equation
H2S(g) +CO(g) → CH3CO2H(g)+ S8(s)
On the left side we have 1x S and on the right side we have 8x S
To balance the amount of S on both sides we have to multply H2S on the left by 8.
8H2S(g) +CO(g) → CH3CO2H(g)+ S8(s)
On the left side we have 16x H and on the right side we have 4x H
To balance the amount of H on both sides we have to multply CH3CO2H on the right by 4.
8H2S(g) +CO(g) → 4CH3CO2H(g)+ S8(s)
On the left side we have 1x C and on the right side we have 8x C
To balance the amount of C on both sides we have to multply C0 on the left by 8. Now the equation is balanced.
8H2S(g) + 8CO(g) → 4CH3CO2H(g)+ S8(s)